Caring Behavior and Emotional Intelligence Among Nurses at Dr. M. Djamil General Hospital: A Cross-Sectional Study - Dorisnita, Dorisnita; Hartati; Nuriyansyah, Melia; Azharman, Zefri (Frontiers on Healthcare Research, 2025)
Background: In carrying out their duties, nurses require social awareness and specific abilities that include intellectual, technical, and interpersonal skills, which are reflected in caring behavior. Caring behavior is essential in nursing practice, grounded in values of kindness, attention, and respect for patients' spiritual beliefs. Some patients at Dr. M. Djamil Padang General Hospital have reported that nurses do not fully address their complaints, feelings, and feedback, and are not responsive to patient calls. Emotional intelligence is considered important because of its role in providing attentive nursing care. Methods: This study used a quantitative design with an observational analytic and cross-sectional approach. The study population consisted of nurses at Dr. M. Djamil Padang General Hospital. Data collection was conducted using questionnaires measuring emotional intelligence and caring behavior. The emotional intelligence questionnaire used The Schutte Emotional Intelligence Scale and the caring behavior questionnaire used the Caring Behaviors Inventory (CBI). Results: The majority of nurses (56.3%) at Dr. M. Djamil Padang General Hospital exhibited high emotional intelligence. Most nurses (95.8%) demonstrated good caring behavior. The analysis showed a significant relationship between emotional intelligence and nurses' caring behavior, but with a weak and negative correlation (r = -0.216, p = 0.019). This means that the higher the nurses' emotional intelligence, the lower the caring behavior tends to be, even though the contribution of emotional intelligence to caring behavior was only 4.7%. Conclusion: Nurses at Dr. M. Djamil Padang General Hospital are mostly between 30-40 years old, female, and Ners graduates. The nurses possess high emotional intelligence and demonstrate good caring behavior. There is a significant relationship between emotional intelligence and nurses' caring behavior, but with a weak and negative correlation. This research suggests that other factors may have a more dominant influence on nurses' caring behavior at Dr. M. Djamil Padang General Hospital.